Peranan Perempuan Dalam Meningkatkan Kesejahteraan Taraf Hidup Keluarga di Desa Kalawat Kecamatan Kalawat Kabupaten Minahasa Utara - Bentian, Beti (Sam Ratulangi University, 2015)
Abstract: The role of women is starting to count as one of the supporting construction. This can be seen not onlyin the social sphere only, in the realm of politics that tends to be the domain of men, but this time have started to enter thefemales, however, from the early observations of researchers towards the implementation of the activities of the nationalprogramme of activities through the role the role of the community through District Development Program (PNPM-PKK)and target the housewife did not seem to conform to expectations with reality.This research was conducted in the village of Kalawat District. Kalawat Minahasa Regency North. The relevance of themethodology with why this area was selected because there is some housewife who follow activities to improve familywelfare role, until researchers argue that by doing research on the location of these researchers can get credible data. Thestudy lasted for three months starting from May to July 2010.Conclusion the role and the efforts made to enhance the capabilities and skills through education, skills training,coaching continuously in order to get maximum results. The role of the housewife in the village of Kalawat sub-district ofNorth Minahasa Regency Kalawat, then there needs to be provision of education and training in order to increase theability and expertise in accordance with the effort that is being done now by housewives comprehensively andcontinuously so that housewives who followed the program PNPM-PPK gain knowledge that will improve the income andwelfare of their families. For the Government, is expected to further empower existing community by using experts inproviding outreach programs or education and training to the community sesuia with the expertise and effort that theyhavKeywords: Women's Role In Improving The Welfare Of